MEDICAL COMPLICATIONS OF RENAL TRANSPLANT - 2 YEARS' EXPERIENCE AT ARMED FORCES INSTITUTE OF UROLOGY - Baig, Zahid Farooq; Siddiqui, Umair Ahmed; Mahmood, Arshad; Sabir, Haroon; Tareen, Tariq Bashir (Journal of Ayub Medical College Abbottabad, 2018)
Background: Renal transplant is the renal replacement therapy of choice for all patients of chronic kidney disease. The aim of this study was to analyse the trends of medical complications in renal transplant recipients at our centre. Methods: it is a prospective cross sectional descriptive study. All the patients undergoing renal transplant at Armed Forces Institute of Urology from September 2013 to September 2015 were included in the study. The patients were followed prospectively till March 2016 and a complete data about their complications and lab investigations was maintained. Results: This study included a total of 63 patients with a mean duration of follow-up of 14.05 months (±SD 4.45). Infective complications as a group are the commonest complication occurring in over 50% of cases followed by haematological complications (17.5%), new onset diabetes after transplant (15.9%) and transplant dysfunction (14.3%) Cardiovascular complications were seen in only 4.8% cases but with high mortality. Gingival hypertrophy was seen in 4.8% cases. Conclusion: Medical complications are common after renal transplant especially in the early post-operative period. The only way forward is early recognition and aggressive treatment, as delays can cost losses in the form of kidney function, life and higher health care cost. Keywords: Renal transplant; Medical complications; AFIU; Pakistan